Socio-behavioural determinants of maternal near miss: a prospective case control study from a tertiary care centre of India. (4th July 2022) - Agarwal, Neha; Jain, Vanita; Bagga, Rashmi; Sikka, Pooja; Chopra, Seema; Jain, Kajal; Muthyala, Tanuja
Abstract: Near miss occurs in far greater numbers than maternal deaths and allows a more robust quantification on risk factors and determinants of life-threatening complications. A 'Three delay model' has been proposed in identification of causes of near miss and maternal deaths. There may be delay in seeking and obtaining health care: delay in recognising danger signs and deciding to reach source of care, delay in reaching appropriate source of care and delay in obtaining appropriate and adequate treatments. We compared various delays between near miss cases ( n = 100) and controls ( n = 200). Women who fulfilled criteria of near miss were taken as cases. Women who had obstetrical complications like near miss but were managed successfully and did not reach near miss state were labelled as controls. Near miss were then compared with maternal death. For normally distributed measurable data, outcome was compared using Student's t -test, for non-normally distributed/ordinal data, outcome was compared using Mann–Whitney's test. For categorical/classified data, association with outcome was analysed using Chi-Square test/Fisher's exact test. Delay in all three levels was seen among the groups. Lack of knowledge, non-availability of decision maker, and concern of cost of transport were main contributors of these delays. Impact Statement: What is already known on this subject? Nonavailability of healthcare and low socio-economic status strongly correlate with maternal morbidity and mortality. What do the results of this study add? Lack of knowledge, non-availability of the decision maker, and concern of cost of transport were the main contributors of delay in seeking medical care. Majority of the cases of near miss were attributed to poor utilisation of health resources, ignorance and lack of emergency obstetric care at the primary level. What are the implications of these findings for clinical practice and/or further research? Patient and attendant education to ensure follow-up visits, recognise danger signs and report without undue delay, compliance to dietary modifications, medications given needs to be addressed at every visit to reduce the impact of socio-behavioural determinants on maternal near miss and mortality which are preventable in majority of cases.